2012
DOI: 10.1155/2012/753164
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Medical Students’ Uptake of the 2009 Pandemic Influenza A (H1N1) Vaccine

Abstract: Background. Pandemic influenza vaccination rate amongst healthcare workers in England 2009/2010 was suboptimal (40.3%). Targeting medical students before they enter the healthcare workforce is an attractive future option. This study assessed the H1N1 vaccine uptake rate amongst medical students and factors that influenced this. Methods. Anonymised, self-administered questionnaire at a medical school. Results. The uptake rate amongst 126 medical students offered the vaccine was 49.2% and intended uptake amongst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
0
21
1
2
Order By: Relevance
“…Results demonstrated that less than half of students surveyed (43%) reported receipt of the seasonal influenza vaccine. The findings are lower than many of the previous studies which focused on medical students [ 12 17 ]. These low uptake results were concerning, particularly considering 68% of the sample were seniors soon to be exiting the program with an undergraduate degree in public health education.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Results demonstrated that less than half of students surveyed (43%) reported receipt of the seasonal influenza vaccine. The findings are lower than many of the previous studies which focused on medical students [ 12 17 ]. These low uptake results were concerning, particularly considering 68% of the sample were seniors soon to be exiting the program with an undergraduate degree in public health education.…”
Section: Discussioncontrasting
confidence: 83%
“…Several studies have examined seasonal influenza vaccination rates specifically among medical students and residents. US medical student and resident seasonal influenza vaccination rates have been found to range from 48 to 58% [ 12 17 ]. Outside of studies focused on students pursuing medical degrees, there have been few assessing influenza vaccination habits of general college students, with existing research finding vaccination rates from 8 to 30% [ 18 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among undergraduate students in 2007 found that 29% of students believed they would get influenza as a result of receiving the vaccine [ 10 ]. Additionally, a study conducted among medical students in England found the strongest barriers to acceptance of the vaccine included fear of side effects, lack of vaccine information, lack of perceived risk, and inconvenience [ 13 ]. The purpose of this study is to identify factors and barriers associated with the receipt of the seasonal influenza vaccine among undergraduate students at a public university.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, durante la pandemia de influenza A (H1N1) en 2010, su adhesión a la vacunación fue de 91%; sin embargo, la cobertura para la temporada de 2011 cayó a 42%. Los argumentos principales para este incumplimiento fueron: la falta de tiempo, el olvido, el miedo a los efectos secundarios, la falta de información sobre las vacunas, la falta del riesgo percibido y las molestias en el sitio de aplicación; incluso, 61% eligió seguir asistiendo a clases aun estando enfermos [22][23][24][25] .…”
Section: Punto De Vistaunclassified